Peran Kesadaran Acara, Atraksi Acara, Selebriti, dan Lokasi Acara Terhadap Minat Cosplayer Menghadiri Chibicon Surabaya - Sugianto, Michelle Natali; Wijaya, Verina (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2026)
Limited understanding among Event organizers regarding the key factors influencing cosplayers’ interest in attending Japanese-themed Events may lead to a decline in cosplayer attendance. To identify the factors affecting cosplayers’ interest, a quantitative approach was employed using a survey method involving 118 cosplayer respondents selected through purposive sampling based on predetermined criteria. Data were collected via an online questionnaire using Google Forms and analyzed with the assistance of SPSS software. The results indicate that Event awareness, Event attractions, celebrity presence, and Event location have a positive influence on cosplayers’ interest in attending Chibicon Surabaya. These findings highlight the importance of effective promotional strategies, relevant Event attractions, and accurate cosplayer segmentation in enhancing the success of Japanese-themed Events organized by Event organizers. Keywords: event awareness, event attractions, celebrity, event location, cosplayer’s interest